Implementation of Cryptography for Database Security in a QR Code and Web-Based Student Attendance System - Somaida, Mochammad Hasymi; Hakim, Walidy Rahman; Ratih, Ratih; Yusuf, Dede (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Non-formal education such as TPQ plays an important role in shaping the character and religious understanding of the younger generation. However, the use of a manual attendance system at TPQ Assayuti is prone to errors, delays in reporting, and a lack of transparency for parents, thereby hindering management accountability. This study aims to develop a web-based attendance system for students with QR Code integration as a more efficient, accurate, and real-time attendance recording solution. The method used is the Waterfall approach, which includes needs analysis, design, implementation, testing, and evaluation. The system enables automatic attendance recording using QR Codes and provides integrated daily reporting features. The implementation results show improved recording efficiency, minimal data errors, ease of monitoring attendance through a responsive dashboard, and positive user feedback regarding ease of use. These findings confirm that the integration of QR codes and web applications effectively supports the digitization of TPQ administration, improves data accuracy, and can serve as a model for the application of information technology in similar religious educational institutions.